Eleusis huanglongensis, a new subcortical species of unmargined rove beetles (Coleoptera: Staphylinidae: Osoriinae) from Sichuan, China - Ma, Hong-Ye; Li, Yang; Yang, Baolin; Lü, Liang (Zootaxa, 2025)
A new species, Eleusis huanglongensis Lü, is described from Songpan County, Sichuan, China. The new species is readily distinguished from E. humilis Erichson, 1840 by distinct morphological characters of the head and temples, as well as the presence of a bi-lamellar internal prominence within the aedeagus. It differs from E. terminata in overall coloration, the degree of ocular prominence in males, and the eye-to-temple ratio in females. In comparison to E. pusilla, E. persimilis, and E. xizangensis, our new species is obviously different in body size and exhibits diagnostic differences in mandibular structure and eye-to-temple ratio. Notably, this represents the first documented occurrence of Eleusis species within the inland provinces of China. A detailed morphological description and diagnostic illustrations of the new species are provided to facilitate identification and comparative assessment.